2000
DOI: 10.1002/(sici)1097-0010(20000515)80:7<939::aid-jsfa644>3.3.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Plant sterols: biosynthesis, biological function and their importance to human nutrition

Abstract: Plant sterols are an essential component of the membranes of all eukaryotic organisms. They are either synthesised de novo or taken up from the environment. Their function appears to be to control membrane¯uidity and permeability, although some plant sterols have a speci®c function in signal transduction. The phytosterols are products of the isoprenoid pathway. The dedicated pathway to sterol synthesis in photosynthetic plants occurs at the squalene stage through the activity of squalene synthetase. Although t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
383
3
41

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 289 publications
(433 citation statements)
references
References 0 publications
6
383
3
41
Order By: Relevance
“…Squalene is a 30-carbon naturally occurring triterpene ( Figure S1, ESI) which herein we use as a model organic aerosol. It has a vital role in the synthesis of sterols in animals and plants 23,24 and is also produced by human skin 25,26 and found as an ingredient in many household oils, used for cooking and frying 27 . Due to skin shedding (desquamation), squalene containing skin flakes are likely a major constituent of indoor dust and hence aerosol.…”
Section: Introductionmentioning
confidence: 99%
“…Squalene is a 30-carbon naturally occurring triterpene ( Figure S1, ESI) which herein we use as a model organic aerosol. It has a vital role in the synthesis of sterols in animals and plants 23,24 and is also produced by human skin 25,26 and found as an ingredient in many household oils, used for cooking and frying 27 . Due to skin shedding (desquamation), squalene containing skin flakes are likely a major constituent of indoor dust and hence aerosol.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that minor components of the diet, such as plant sterols or phenolic compounds, can affect consumer health (Parr & Bolwell, 2000;Piironen et al, 2000;Ostlund et al, 2002), and thus we also aimed to identify an unknown substance found in the neutral lipid (NL) fraction of reindeer meat during fatty acid analyses (Sampels, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Such a risk estimation might be further influenced by the presence of postprandial hyperlipidemia (Ebenbichler et al, 1995). Dietary products with a lipid-lowering and/or antioxidative capacity may be important in the reduction of risk of coronary heart disease (Hollman et al, 1996;Piironen et al, 2000). Flavonoids, which have been shown to exert antioxidant actions, have been extensively studied.…”
Section: Introductionmentioning
confidence: 99%